EFEKTIVITAS SISTEM INFORMASI MANAJEMEN DAN AKUNTANSI BARANG MILIK NEGARA (SIMAK-BMN) TERHADAP PENGELOLAAN ASET NEGARA - Edy Nasrudin (Universitas Jember, 2015)
Information Systems and Management of State Assets (SIMAK-BMN) is a series of data collection procedures of state property were obtained from the state budget funds to a government entity (satuan kerja) to be processed into information administration of state assets in the balance sheet in Financial Report. This system can meet the managerial and accountability at once. In practice, this system has been formulated in the form of computer-based applications that have been implemented since 2005. Although during this application has gone well, the writing of this paper aims to look at the effectiveness of the system by analyzing the application of SIMAK-BMN application field by scientific literatur related to it. Not only in term of its application tools but also on the user side application, because data collection is done manually by the user application SIMAK-BMN. Effectiveness of Information SIMAK-BMN measure of the level achievement of the objectives the system, namely the administration of state property is good and the high level of accountability in the report of state property and financial report. Because SIMAK-BMN is a subsystem of Institution Accounting System to produce financial statements. The higher the quality of financial statement, meaning the effective implementation of SIMAK-BMN.